A proposed solar streetlight design towards energy efficiency for Universiti Tun Hussein Onn Malaysia (UTHM) / Liew Pok Huai and Zainal Abidin Akasah - Liew, Pok Huai; Akasah, Zainal Abidin (2018)
Street lighting is an essential public service that provides a safer environment at nighttime to commuters as well as pedestrians. Proper use of street lighting can be considered as a protective method that provides economic and social benefits to the people. However, the conventional streetlight had caused some serious problems. Long periods of wind, rain and sun exposure, low waterproof performance, and poor wire insulation have caused electricity leakage of conventional streetlight that may prove potentially great harm to people. Besides, the conventional street light requires great energy consumption. Therefore, the objectives of this research project are to identify the disadvantages of using conventional streetlights, to compare the energy efficiency, cost and safety of solar streetlights with the conventional streetlights, and to produce a proposed design for solar streetlights. The study location of this project is on the main campus of Universiti Tun Hussein Onn Malaysia (UTHM). In this project, four main processes had been conducted which are data collection process, analysis process, process of comparison, and the design process. With the data collection, an analysis had produced the current practicability of conventional streetlight, and a comparison with solar streetlight was conducted.